Социально-экономические аспекты мультипарного удлинения нижних конечностей по методу Блискунова - Бобарыкина, Е.Н.; Федуличев, П.Н. (Культура народов Причерноморья, 2013)
В статье рассматриваются медицинские и социально-экономические аспекты применения
мультипарного дистракционного остеосинтеза нижних конечностей по методу А.И. Блискунова и
преимущества данного оперативного вмешательства перед другими методиками внутрикостной
дистракции как с точки зрения экономического эффекта, так и скорейшей реабилитации пациента и
его способности к самообслуживанию в послеоперационный период. У статті розглядаються медичні та соціально - економічні аспекти застосування
мультіпарного дістракційного остеосинтезу нижніх кінцівок за методом О.І. Блискунова та переваги
даного оперативного втручання перед іншими методиками внутрікісткової дистракции як з точки зору
економічного ефекту, так і якнайшвидшої реабілітації пацієнта і його здатності до
самообслуговування у післяопераційний період. The article discusses the medical and socio - economic aspects of multipair distraction osteosynthesis
of the lower limbs by the method of A.I. Bliskunova and benefits of surgery over other methods of intraosseous
distraction from the point of view of economic efficiency and the rapid rehabilitation of the patient and his
capacity for self-care in the postoperative period. Terms and conditions for the provision of this type of care,
convalescence and rehabilitation not only affect the cost of medical institutions , but also on the costs of the
Social Insurance Fund on a temporary loss of ability to work (on payment certificate of incapacity ), the cost of
the patient. The need for constant medical care in the postoperative period, and in the process of fixation, as
well as limited mobility and the possibility of an independent household and physiological effects not only entail
additional costs, but also the impact on the psycho- emotional state of the patient. Inability to full self-service
and the need to constantly refer to the help from the outside affects the patient's mood and self-esteem
(especially in the first post-operative phase of treatment). After a certain psychological adjustment, and as you
move the treatment , the patient's emotional state changes. There are also gender and age, and especially the
reaction of patients on concomitant transosseous fixation physiological and dermatological problems .